Two-dimensional melting of polydisperse hard-disk system with pinning - Hu, Guoyu (2019)
The melting transition of the two-dimensional system is one of the famous unresolved questions in phase transformations that attract physicists’ attention continuously. One unique feature of two-dimensional melting is the hexatic phase formed predicted by Kosterlitz-Thouless-Halperin-Nelson-Young (KTHNY) theory. However, the stability region of the hexatic phase is very small and it can hardly be observed in most systems. Recently, two methods, increasing polydispersity and random pinning a small fraction of particles, showed promising effects of enlarging the hexatic region. In this study, we implemented a modified Event-Chain Monte Carlo method to study the combined effects of these two factors on a hard-disk system. The phase diagram is calculated, and the transition points are significantly shifted that results in a stable hexatic phase over a wide range of density.